Fast-Dissolving Sublingual Nanofibers of Ondansetron Hydrochloride: Formulation, Physicochemical Characterization, and Clinical Evaluation on Post-cataract Surgery Patients - Samira Kamranpour; Shahla Mirzaeei; Farid Daneshgar; Farid Najafi (Tabriz University of Medical Sciences, 2022)
Background: Ondansetron hydrochloride (OND) is an antiemetic agent belongs to the 5-HT3 receptor antagonist class administrated widely in relieving nausea and vomiting which is the most common complication occurred after surgery. This study aimed to design and evaluate the physicochemical along with clinical effects of fast-dissolving nanofiber (FDN) of OND administrated sublingually to enhance the bioavailability, effectiveness, and patient compliance compared to orally disintegrating tablets (ODT). Methods: Nanofibers were prepared by the electrospinning method, using polyvinyl alcohol and alpha-cyclodextrin as polymers and sodium saccharin as the sweetener. Physicochemical and mechanical characteristics of nanofibers were examined then the clinical evaluation was performed. Eighty patients volunteering for cataract surgery were randomly divided into two groups, one received FDN, and the other treated with ODT of OND after recovery and in case of relieving nausea. The severity of nausea was assessed using a visual analogue scale in the 6 and 24 h intervals after drug administration. The SPSS 25.0 statistical software and statistical tests were used to analyze the obtained data. Results: Nanofibers possessed a mean diameter of 159 ± 30 nm beside suitable physicochemical and mechanical characteristics. Statistical evaluations showed that both FDN and ODT formulations had an equal anti-emetic effect (P>0.05) on reducing the severity of nausea but the FDN formulation caused significantly higher levels of patients' satisfaction (P<0.05) compared to the ODT. Conclusions: Although both formulations had an almost equal anti-emetic effect, due to the benefits of this novel formulation including rapid disintegration, the ODT can be replaced by FDN.